2019
DOI: 10.1590/1806-3713/e20170080
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smoking and reasons for continuing to smoke: a population-based study

Abstract: Objective: To investigate the prevalence of smoking and the reasons for continuing to smoke among adults in Brazil. Methods: This was a cross-sectional, population-based study including 1,054 individuals ≥ 40 years of age, residents of the city of Florianopolis, Brazil, of whom 183 were smokers. All of the smokers completed the University of São Paulo Reasons for Smoking Scale (USP-RSS). Depressive symptoms were evaluated with the Hospital Anxiety and Depression Scale, and spirometry was performed to screen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
14
0
5
Order By: Relevance
“…It is used in the form of smoke due to the pleasurable rewarding effect of its active constituent nicotine. 32 , 33 The global projected prevalence of current users of some form of tobacco among people aged 15 years and above is 22.8%. Ethiopia accounts for more than 2.6 million current tobacco smokers based on the population estimates published by the United Nations Population Division.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in the form of smoke due to the pleasurable rewarding effect of its active constituent nicotine. 32 , 33 The global projected prevalence of current users of some form of tobacco among people aged 15 years and above is 22.8%. Ethiopia accounts for more than 2.6 million current tobacco smokers based on the population estimates published by the United Nations Population Division.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking intensity could re ect short-term exposure levels and it was divided into three categories: current light smoker (< 70 cigarettes per week), moderate smoker (≥ 70 and < 140 cigarettes per week) and heavy smoker (≥ 140 cigarettes per week) 18 . Smoking burden which was a comprehensive indicator of smoking amount and duration, was divided into two categories according to the median level: lower burden (< 20 pack-years) and higher burden (≥ 20 pack-years) 19 . Pack-years of smoking was de ned as the product of the average number of packs of cigarette smoked per day multiplied by the average days of smoking in one year.…”
Section: Ascertainment Of Tsementioning
confidence: 99%
“…A recent study was conducted by Rocha et al, (2019) prevalence of smoking and the reasons for continuing to smoke among adults in Brazil in 2019. They conducted a cross-sectional population-based study of the population.…”
Section: Consumer Psychologymentioning
confidence: 99%
“…A recent study conducted in Brazil by Rocha et al, (2019) to investigate the prevalence of smoking and the reasons for continuing to smoke among adults in Brazil revealed that racial and ethnic differences can have a significant influence on the prevalence, patterns, health implications and consequences of smoking. The followings are the predetermined reasons for smoking determined in this study; physical dependence, the pleasure of smoking, tension reduction, stimulus, automatism, handling, social smoking, weight control, and close association.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%